Tinjauan Mini: Perkembangan Teknologi dan Tantangan Mobil Listrik dalam Dekade Terakhir - Lutfi Pramudya Faizhata; Khoirul Huda (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Over the past decade, electric vehicles (EVs) have experienced significant development and become a focal point of the global agenda for sustainable transportation. This study aims to systematically examine the technological dynamics and challenges of electric vehicle implementation, particularly in the context of developing countries like Indonesia. The method used was a PRISMA-based Systematic Literature Review (SLR) of relevant scientific articles published between 2020 and 2024. The study results show significant progress in battery technology, including the development of solid-state and artificial intelligence-based management systems for in-wheel electric motors, fast charging systems, and the integration of AI- and IoT-based connectivity. However, key challenges remain, including limited infrastructure, high initial costs, interoperability issues, and cybersecurity risks. In the Indonesian context, structural constraints such as the distribution of charging stations and the lack of fiscal incentives have hampered the widespread adoption of EVs. These findings underscore the need for an interdisciplinary approach and integrated policies to accelerate the transition to inclusive and efficient low-emission mobility. This study provides an academic contribution through a comprehensive mapping of technological developments and offers practical implications for the formulation of future transportation strategies.